Sistem Kendali Navigasi Ar Drone Menggunakan Leap Motion - Andyan Bina Ardhana; Gembong Edhi Setyawan; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The technology is highly developed from various aspects without the crew one quadcopter. the majority still use a quadcopter applications Android-based. simple movements control can make to control the quadcopter. Emergence of innovation of Natural User Interfaces (NUI), language human-like voice, movement, or view to communicate with quadcopter technology. In the system research created a control harness innovation from NUI quadcopter from users. The user's hand be detected using leap motion. Leap motion is a device where optical and infrared sensors to detect a hand gesture. Leap motion and quadcopter programmed either using javascript. and speed, the resulting percentage accuracy of movement of 100%.the generated quadcopter to movement of the pitch, roll, yaw, gaz that is directly proportional to the value obtained from the user's movement, this indicates when the input from the user, then the greater the quadcopter will grow quickly and so vice versa. the system delay is the user moves the hand in accordance with quadcopter user instruction generates a delay of 0,26 seconds.